A Single Site Phosphorylation on Hsp82 Ensures Cell Survival during Starvation in Saccharomyces cerevisiae. Issue 21 (2nd October 2020) - Shang, Xuan; Cao, Guang; Gao, Han; Li, Melinda; Peng, Guanzu; Ji, Yanqiu; Zhang, Yansong; Zhang, Wenzhe; Li, Wanjie; Dou, Fei
Abstract: Unicellular organisms live under diverse stressful conditions and must respond and adapt quickly to these stresses. When these stresses persist, cells favor a transition to quiescence. There are changes to many processes when cells begin their entry into quiescence. It has been reported that Hsp82 plays an important role in several such processes, and its distribution and activity change according to nutrient conditions. In this study, we found that the subcellular distribution of Hsp82 is regulated by its co-chaperone Ppt1. Under starvation conditions, Ppt1 expression was significantly reduced by a TOR-independent pathway. Furthermore, we found that Ppt1 regulates Hsp82 distribution in the cytoplasm and nucleus by dephosphorylating the S485 residue on Hsp82. The Hsp82 S485A strain has impaired membrane-related protein transport, and its cell size did not become larger in quiescence compared to log phase, resulting in failure to survive during starvation. Graphical abstract: (Left) Under nutrient-rich conditions, the TOR pathway maintains active, which inhibits the activity of kinase X. High-level expression of Ppt1 dephosphorylates Hsp82. Dephosphorylated Hsp82 shuttles between the cytoplasm and nucleus. (Right) Under starvation conditions, Hsp82 could not be dephosphorylated by Ppt1 due to the drop-in expression of Ppt1. The kinase X is activated due to the inactivated of the TOR pathway. Kinase X phosphorylates Hsp82 causing its nuclear accumulation. Phosphorylated S485 on Hsp82 is required for the membrane-related protein transport, resistant to the cell wall drugs and heat shock and controlling of cell size. Thus, phosphorylated Hsp82 on S485 ensures cell survival under starvation conditions. Unlabelled Image Highlights: Hsp82 distributes in the cytoplasm and nucleus uniformly in nutrient-rich conditions. Hsp82 accumulates in the nucleus under starvation and consequent quiescence. Ppt1 dephosphorylates the S485 residue on Hsp82 in nutrient-rich conditions. Hsp82 S485A fails to accumulate in the nucleus under starvation conditions. Ppt1-Hsp82-mediated nutrient-sensing pathway ensures cell survival during starvation.